2020
DOI: 10.1007/s11517-020-02203-y
|View full text |Cite
|
Sign up to set email alerts
|

In silico validation of electrocardiographic imaging to reconstruct the endocardial and epicardial repolarization pattern using the equivalent dipole layer source model

Abstract: The solution of the inverse problem of electrocardiology allows the reconstruction of the spatial distribution of the electrical activity of the heart from the body surface electrocardiogram (electrocardiographic imaging, ECGI). ECGI using the equivalent dipole layer (EDL) model has shown to be accurate for cardiac activation times. However, validation of this method to determine repolarization times is lacking. In the present study, we determined the accuracy of the EDL model in reconstructing cardiac repolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…However, given the more complex nature of repolarization compared to activation (i.e., less voltage differences, the effect of cardiac motion, and more difficulty in reliably obtaining gold standards), this is more complicated. In a previous in silico study, we have shown that this method gives accurate results in reconstructing RTs (van der Waal et al, 2020).…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…However, given the more complex nature of repolarization compared to activation (i.e., less voltage differences, the effect of cardiac motion, and more difficulty in reliably obtaining gold standards), this is more complicated. In a previous in silico study, we have shown that this method gives accurate results in reconstructing RTs (van der Waal et al, 2020).…”
Section: Introductionmentioning
confidence: 86%
“…The inverse computation was performed using the EDL method, as previously described in the study by van der Waal et al (2020). A brief explanation is given in this study.…”
Section: Ecg Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…This regularization methodology was used on this manuscript as their intrinsic parameter (L-curve curvature) allows to refine the heart anatomy as a secondary outcome. However, the use of Tikhonov regularization on the location process do not become a limitation, once the heart is properly located, to the use of novel and more accurate inverse-problem methodologies enabling better ECGI reconstructions and/or including transmural differences [32][33][34].…”
Section: Ecgi Reconstruction and Inverse Solutionmentioning
confidence: 99%